Pengaruh Intellectual Capital terhadap Kinerja Keuangan pada PT. Bank Rakyat Indonesia dan PT. Bank Negara Indonesia - Amilia Paramita Sari (Universitas Batanghari Jambi, 2021)
This research aims to test the influence of intellectual capital on the performance of the company. Intellectual Capital is measured by the VAIC method which has three variables namely Value Added Capital Employed, Value Added Human Capital and Structural Capital Value Added, while the company's performance is measured using Return on Assets. This study uses PT. Bank Rakyat Indonesia and PT. Bank Negara Indonesia data during the period 2015-2020. The analysis method used is regression analysis. The results of this study prove that only Value Added Human Capital and Structural Capital Value Added have a significant positive effect on Return on Assets. The Value Added Capital Employed has no effect on Return on Assets. This shows that PT. Bank Rakyat Indonesia and PT. Bank Negara Indonesia still rely on their physical assets as measured by physical capital followed by human capital in creating added value for the company which ultimately has an impact on improving bank performance.